Démocratisation de l'accès au diplôme et validation des acquis de l'expérience : une avancée sociale ? - Fabienne Maillard (Les éditions de la Maison des sciences de l'Homme, 2007)
After having promoted the democratisation of the education system and of vocational training, public policies in France developed professional certifications and increased the number of their holders. New individual rights came along with certification, which cast the individual as an actor of his/her professional life. This article questions the bases of this project and its prospects. It tends to certify the productive qualities of the individuals without guaranteeing anything back. Holding a diploma becomes a norm, intended to bring fluidity to the labour market and reinforce the employability of individuals. Far from being a measure at the service of individual workers, it is conceived as an instrument for employers to select and manage the workforce.